Pengaruh Latihan Koordinasi Gerak dan Latihan Core Stability Terhadap Peningkatan Kesesuaian Gerak Dan Kecepatan Renang Gaya Dada - Ramadan, Dikdik Najmu; Suhartini, Bernadeta; Anugrah, Sendy Mohamad; Triprayogo, Rian (Institut Teknologi Bandung, 2024)
This study examines the effect of movement coordination and core stability training on increasing the suitability of movements and speed of breaststroke swimming. The sample in this study amounted to 20 people who were taken using purposive sampling technique, then ordinal pairing was carried out to divide each group, the control group (not getting training) and the experimental group (getting training). The research method used in this study was a quasi-experimental with a nonequivalent control group design pattern. The parameters used to measure the suitability of movement are the breaststroke swimming movement suitability analysis indicator form, while the swimming speed is a 50-meter breaststroke swimming test. The results showed that movement coordination training and core stability training significantly increased the suitability of movement and swimming speed, with a significance value of p <0.05. The greatest increase was seen in athletes in the experimental group, especially in athletes with age categories III and IV, compared to the control group. Thus, athletes will get a training pattern that suits their respective characteristics, so that they feel comfortable and motivated in the training process towards achieving training goals. For further research, data collection on the suitability of breaststroke movements was carried out using a video camera so that the movement assessment was clearer and more detailed.